Evaluation of computer-aided software engineering tools: experience from Malaysian organisations - Selamat, Mohd Hasan; Rahim, Md Mahbubur (Elsevier, 1996)
Computer-aided software engineering (CASE) technology has been adopted by the Western information systems community for a decade. However, CASE is new in Malaysia, and little is known about its use and effects on the software development tasks within the Malaysian context. This paper evaluates CASE technology in terms of its impacy on productivity, software quality and maintanance, and makes reference to a survey that was carried out into the use of CASE tools in 40 Malaysian organisations. Survey results reported an uneven improvement in productivity that varied across the stages of the life cycle. Productivity was also found to vary depending on the types of CASE softwate. Additional results revealed that upper CASE tools contributed more towards the improvement of software quality, while lower CASE tools were rated higher for maintenance reduction. However, CASE technology was not successful in all organisations. People issues related to CASE implementation caused CASE failures in some of the surveyed organisations. The findings of the survey were further compared with the European, Australian and US studies, and interesting differences were highlighted.